Reconnecting with Nature: Reflections of The Concepts of Biophilia and Biomimicry in Interior Design - Dolu, Dürdane Aksoy; Burkut, Emine Banu (Lublin University of Technology, 2025)
This study critically examines the integration of biophilic design and biomimicry as complementary, nature-inspired strategies to promote sustainability and human well-being in interior architecture. While biophilic design aims to re-establish the emotional and psychological connection between humans and nature through direct and indirect natural elements, biomimicry focuses on imitating the functional intelligence of nature to develop energy-efficient, adaptable, and ecologically responsible solutions. Despite frequent conceptual overlaps in the literature, this research isolates their unique principles and explores their synergistic potential in the context of interiors. Using bibliometric analysis tools such as Web of Science, Scopus, VOSviewer, and R Studio Bibliometrix-Biblioshiny, the study maps publication trends, thematic networks, and underexplored research areas. While the findings reveal a growing academic interest in these concepts, they also highlight a significant gap between theoretical discourse and real-world application. The study advocates evidence-based integration of biophilic and biomimetic principles, supported by interdisciplinary collaboration and empirical case studies. Ultimately, the research offers actionable insights for academics and design professionals aiming to create indoor environments that balance user-centred well-being with environmental responsibility.
Keywords: Biophilia; Biomimicry; Nature-based design; Sustainability; Interior design; Nature-inspired interiors